2012
DOI: 10.1371/journal.pone.0038327
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Copper Elevation in a Mouse Model of Wilson's Disease Is a Regulated Process to Specifically Decrease the Hepatic Copper Load

Abstract: Body copper homeostasis is regulated by the liver, which removes excess copper via bile. In Wilson's disease (WD), this function is disrupted due to inactivation of the copper transporter ATP7B resulting in hepatic copper overload. High urinary copper is a diagnostic feature of WD linked to liver malfunction; the mechanism behind urinary copper elevation is not fully understood. Using Positron Emission Tomography-Computed Tomography (PET-CT) imaging of live Atp7b−/− mice at different stages of disease, a longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 32 publications
8
91
0
Order By: Relevance
“…[ 64 Cu]CuCl 2 -PET/CT imaging of Balb/c mice was performed using a method described previously [79, 13]. Briefly, Balb/c mice were anesthetized by 3% isoflurane in 100% oxygen (3 L/min) at room temperature, using an isoflurane vaporizer (Summit Anesthesia Solutions, Salt Lake City, UT).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 64 Cu]CuCl 2 -PET/CT imaging of Balb/c mice was performed using a method described previously [79, 13]. Briefly, Balb/c mice were anesthetized by 3% isoflurane in 100% oxygen (3 L/min) at room temperature, using an isoflurane vaporizer (Summit Anesthesia Solutions, Salt Lake City, UT).…”
Section: Methodsmentioning
confidence: 99%
“…Positron emission tomography (PET) is a useful technology for functional imaging of cerebral metabolic activity in vivo based on its high sensitivity and quantification capability. Recently, biodistribution and radiation dosimetry of [ 64 Cu]CuCl 2 in Atp7b −/− knockout mice, a well-established mouse model of WD [6], was determined by PET/CT analysis [79]. Exploring feasibility and use of [ 64 Cu]CuCl 2 as a tracer for noninvasive assessment of changes of cerebral copper metabolism in WD, this study aimed to assess age-dependent changes of 64 Cu radioactivity in the brains of Atp7b −/− knockout mice using PET/CT, following intravenous injection of [ 64 Cu]CuCl 2 as a tracer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When added to HEK293 cells, SCC competed with the radioactive Cu for the uptake by Ctr1, further indicating that SCC could be a source of Cu for cells. 22 Finally, experiments with cultured cells first loaded with Cu and then washed and placed in a serum-free medium revealed that cells secrete Cu in a complex with SCC or the SCC-like molecule. This result is interesting, as it suggests that SCC interacts and forms complex with Cu within the cell, probably within the secretory pathway.…”
Section: Cu Entrymentioning
confidence: 99%
“…Approximately 50% of copper is excreted in bile and the rest in other intestinal secretions (saliva, gastric, pancreatic and small intestinal). Normally, 10–15% of copper in bile is reabsorbed, but this is an important mechanism of copper homoeostasis and biliary excretion declines in hypocupraemia,7 and, conversely, biliary excretion increases in the presence of high free copper levels in blood, through the action of ATP7B, the copper transporter inactivated in Wilson's disease 8. If this second hypothesis is correct, it shows the importance of the secretion of free copper into the gut, even when given intravenously in large amounts.…”
Section: Discussionmentioning
confidence: 99%